Pre- and Post-COVID-19 Antibiotic Consumption and Stewardship Program in a Southern Italian Hospital - Maria Costantino; Valentina Giudice; Federica Campana; Alessandra Anna Iannelli; Pasqualina Scala; Walter Longanella; Francesco Marongiu; Emilia Anna Vozzella; Maria Giovanna Elberti; Maria Alfieri; Giovanni Boccia; Valeria Conti; et al. (Antibiotics)
Background/Objectives: Antibiotic resistance is a growing global threat that significantly impacts public health and healthcare costs. The Italian National Action Plan on Antimicrobial Resistance (PNCAR) was introduced in 2017 to address this issue by improving antibiotic stewardship. This study aimed to evaluate the effectiveness of the PNCAR in enhancing antibiotic management practices in a hospital in southern Italy before and after its implementation. Methods: We conducted an observational monocentric study to analyze antibiotic consumption in a hospital setting before and after the COVID-19 pandemic (2019 and 2023) and to examine prescription appropriateness and the types of used antibiotics. Results: After PNCAR introduction, we recorded a significant increase in antibiotic prescription appropriateness and in Access antibiotic and targeted therapy usage, while Reserve antibiotics were prescribed in ~10% of the cases, with an increasing trend in 2023. Conclusions: Our study supports the importance of targeted stewardship initiatives, including continuous monitoring and education, to sustain antibiotic prescription appropriateness and to reduce antimicrobial resistance.